THE COMPLETE COMPUTER UPGRADE & REPAIR BOOK - SCHMIDT A CHERYL (USA DREAMTECH PRESS SCOTT/JONES INC publishers`, 2007)
"The Complete Computer Upgrade & Repair Book" by Cheryl A. Schmidt is a detailed, hands-on guide that serves as both a textbook and a practical reference for PC maintenance and hardware. It is written for students, aspiring technicians, and hobbyists, providing a foundational understanding of all major personal computer components, including motherboards, processors, RAM, storage devices, and peripherals. The book systematically covers the essential skills of a computer technician, focusing on how to assemble a PC, install operating systems, perform system upgrades, and, most critically, how to diagnose and troubleshoot a wide range of common hardware and software problems. It acts as an all-in-one resource for learning how to safely and effectively repair and upgrade microcomputers.
COMPUTER UPGRADE & REPAIR
COMPUTERS
Keywords: COMPUTERS